Synthesis of an azido-tagged low affinity ratiometric calcium sensor. Issue 51 (23rd December 2015) - Caldwell, Stuart T.; Cairns, Andrew G.; Olson, Marnie; Chalmers, Susan; Sandison, Mairi; Mullen, William; McCarron, John G.; Hartley, Richard C.
Abstract: Changes in high localised concentrations of Ca 2+ ions are fundamental to cell signalling. The synthesis of a dual excitation, ratiometric calcium ion sensor with a K d of 90 μM, is described. It is tagged with an azido group for bioconjugation, and absorbs in the blue/green and emits in the red region of the visible spectrum with a large Stokes shift. The binding modulating nitro group is introduced to the BAPTA core prior to construction of a benzofuran-2-yl carboxaldehyde by an allylation–oxidation–cyclisation sequence, which is followed by condensation with an azido-tagged thiohydantoin. The thiohydantoin unit has to be protected with an acetoxymethyl (AM) caging group to allow CuAAC click reaction and incorporation of the KDEL peptide endoplasmic reticulum (ER) retention sequence. Graphical abstract: